Body injury in the elderly victims of fall in public transportation. - Blanco, Priscilla Hellen Martinez; Gimenes, Régio Marcio Toesca; Silva, Eraldo Schunk; Cortez, Lucia Elaine Ranieri (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: Body injury due fall can happen in all subjects, but this risk increases in the elderly due to the inherent changes of aging itself. Moreover, the public mass transit system is not adapted to the needs of this population on the rise. Objective: The objective of this research was to describe and analyze injuries by body segment in the elderly victims of fall in the public transport of Maringa. Method: Cross-sectional, descriptive, retrospective and quantitatively through analysis of patient records of the occurrence of falls in the elderly aged over 60 years in the collective transport of Maringa between the period 2005 to 2012, where we analyzed the following variables: gender, age and injured segment. Data were analyzed using descriptive statistics and the Kruskal - Wallis test. Results: The results showed an increase in the number of falls in transport in the city and in 2012 (60%) of these events were elderly, most cases of falls is in females (69% of cases) and body segments more injured were members. Conclusion: We conclude that in Maringa women are the most frequent victims of falling in public transport and the most significantly injured segment are the upper and lower limbs.